2011
DOI: 10.1021/ja2092322
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Mechanical Model of Cholesterol/Phospholipid Mixtures: Linking Condensed Complexes, Superlattices, and the Phase Diagram

Abstract: Despite extensive studies for nearly three decades, lateral distribution of molecules in cholesterol/phospholipid bilayers remains elusive. Here we present a statistical mechanical model of cholesterol/phospholipid mixtures that is able to rationalize almost every critical mole fraction (Xcr) value previously reported for sterol superlattice formation as well as the observed biphasic changes in membrane properties at Xcr. This model is able to explain how cholesterol superlattices and cholesterol-phospholipid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 40 publications
2
21
0
Order By: Relevance
“…An alternate view that proposes a longer range, lattice-like substructure in the L o phase of binary mixtures containing cholesterol has been proposed by Chong and coworkers, with the lattice composed of condensed complexes of lipid and cholesterol. 52 …”
Section: Discussionmentioning
confidence: 99%
“…An alternate view that proposes a longer range, lattice-like substructure in the L o phase of binary mixtures containing cholesterol has been proposed by Chong and coworkers, with the lattice composed of condensed complexes of lipid and cholesterol. 52 …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a number of investigators have found the evidence for the existence of relatively large, long-lived lipid rafts in actual biological membranes unconvincing (Edidin, 2003;McMullen et al, 2004;Munro, 2003). Moreover, other workers have provided evidence that Chol may be organized as molecular complexes (Radhakrishnan and McConnell, 1999) or various superlattices (Chong, 1994;Helrich et al, 2006;Huang, 2002;Sugar and Chong, 2012) in phospholipid bilayers, resulting in biphasic or discontinuous changes in some of their physical properties. Whatever the biophysical details, it is clear that the presence of Chol in biological membranes does modulate a number of different membrane functions, either directly or via its effects on the properties and lateral organization of the phospholipid bilayer (Dahl and Dahl, 1988,b;McElhaney, 1992a, b;Yeagle, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…A statistical mechanical model of CHOL-phos pholipid mixtures that is able to rationalize almost any critical mole fraction value previously reported for ste rol superlattice formation as well as the observed biphasic changes in membrane properties was recently presented in paper [263]. According to this model, the extent and the type of sterol superlattices, and thus the lateral distribution of the entire membrane, should vary with CHOL mole fraction in a delicate, predict able, and nonmonotonic manner, which should have profound functional implications.…”
Section: Cholesterolmentioning
confidence: 89%